Different Perspectives on the Global Development of Transport - Ubbels, Barry; Rodenburg, Caroline; Nijkamp, Peter (European Journal of Transport and Infrastructure Research, 2001)
The future of the transport sector is clearly fraught with uncertainties, as the system is influenced by many factors that can develop in various ways. The aim of this paper is to get insight into the future development of the transportation sector seen from a world-wide perspective. This is done by applying a scenario approach and by designing four possible development paths for transport. These future developments are presented here by sketching four global contrast images based on outcomes of earlier research. The outcomes for the transport sector, expressed in transported volumes for both passenger transport and freight transport, are first described qualitatively, based on expected developments of several indicators. Next, based on those descriptions, quantitative numbers of transported volumes are calculated with the year 2020 as the time horizon. It appears that all scenarios foresee a world-wide growth in transport volumes (for both passengers and freight). The achievement of sustainable mobility based on the outcomes presented in this paper may seem difficult and will be confronted with several hurdles. But policy changes and (unexpected) technology developments offer possibilities to realise this objective. Thus policy makers are faced with formidable policy challenges to achieve the Kyoto objectives in the next 20 years.